KORELASI MOTIVASI DAN KEMANDIRIAN DENGAN HASIL BELAJAR SETIAP MUPEL TEMATIK KELAS V SEKOLAH DASAR - Titin Nurul Huda; Bistari Bistari; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe the level of correlation between motivation and independent learning with the learning outcomes of each subject in integrated thematic learning in class V Elementary school 39 Pontianak City. The method used in this research is descriptive with a form of correlation study. The study population was 31 students. Data collection techniques using indirect communication with documentary study techniques. Data collection tools in the form of questionnaires and document student learning outcomes are divided into several subjects. The results of the research that have been done are 90.47% learning motivation is included in the very good category, 90.29% student learning independence is in the very good category and the learning outcomes of each group of students have reached the KKM. Based on statistical analysis using multiple correlation formulas to determine the correlation coefficient between motivation and independence learning with the learning outcomes of each subject, the results are in the medium category. Based on the calculation results, there is a relationship between motivation and independence learning with the learning outcomes of each subject in thematic learning in class V elemntary school 39 Pontianak City. Keyword: Correlation, Learning Motivation, Learning Independence, Learning Outcomes and Integrated Thematic Learning.